Cognitive Emotion Regulation Styles and the Impulsive Behavior of Patients with Substance Use Disorders: A Cross-Sectional Study - Dagli, Dilek Ayakdas; Baysan Arabacı, Leyla; Tas Soylu, Gülsenay; Dayılar Candan, Hatice (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: This study aimed to examine the correlation between the cognitive emotion-regulation styles and impulsive behaviors of patients who has substance use disorder. A total of 197 patients who were receiving inpatient treatment after diagnosis of substance use disorders in the Alcohol and Substance Addiction Treatment Center in two hospitals participated in study. Ethical permissions were obtained. For data collection, Introductory Information Form, Cognitive Emotion Regulation Questionnaire, UPPS Impulsive Behavior Scale were used. Descriptive statistics and correlational analysis and multiple regression analyses were performed. The mean age of the patients was 39.35 ± 12.43 years, and 88.3% of them were male. Among them, 38.9% used alcohol, and 51.8% used substances. There is a correlation between the patients’ cognitive emotion regulation styles and impulsive behavior styles. The multiple regression analysis showed that the patients’ cognitive emotion regulation style explained 20.6% of their impulsive behavior.
Keywords: Addiction; emotion regulation; impulsive behavior; substance use disorder